The Feasibility of Fired Clay Bricks Production From Industrial Waste: Overview on Properties and Potential Environmental Impact - Romli, Muhammad Arif Danial; Abdul Kadir, Aeslina (Recent Trends in Civil Engineering and Built Environment, 2022)
The ever-increasing number of industries and factories development had produced industrial wastes. In consequence, the waste produced are potentially a hazard to the surrounding. Therefore, to solve this problem, a new alternative method to recover the industrial waste such as gypsum waste, electroplating sludge and mosaic sludge into new product was highlighted by incorporating into fired clay brick. This study was conducted to review the properties and the potential environmental impacts of fired clay brick production by utilizing industrial waste based on literatures from previous studies. Previously, the physical and mechanical properties showed that shrinkage was found out that were effective in achieving a result of less than 8%. The increasing addition of industrial waste, the lower the compressive strength and density able to make the size of brick’s pore are larger. In addition, the potential environmental impacts were Life Cycle Assessment (LCA). The previous data showed that traditional brick and industrial waste gives big impact on acidification, global warming and ozone layer depletion. The LCA analysis could provide insight view on the production of fired clay brick incorporated with industrial waste hence could benefit both the industrial and environmental privileges.